Effects of Storytelling in Local Visual Culture Infrastructure on Customer Satisfaction: The Mediating Effects of Brand Equity (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Focusing on brand equity, this study explored the impact of storytelling, a variable that influences local visual culture infrastructure, on customer satisfaction. Data for quantitative study were collected from four different cases including smallsized cinemas and public media centers. The collected data were analyzed using descriptive statistics, exploratory factor analysis, and structural equation modeling to identify causal relationships between variables. Through theoretical consideration, storytelling was extracted as the significant influencing variable on customer satisfaction in local visual culture infrastructure. This study found that the effects of storytelling are mediated by brand equity. Going forward, further research needs to be conducted to explore diversified variables influencing customer satisfaction in local visual culture infrastructure.